2017
DOI: 10.32890/ijms.25.1.2018.10495
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Entrepreneurial Orientations in Talent Retention Amongst Malaysian Engineers

Abstract: This paper examines the linkage between entrepreneurial orientation (EO) and talent retention amongst Malaysian engineers from the perspective of entrepreneurial orientation theory.A cross-sectional survey of 104 engineers from private organisations in Malaysia was conducted to test the hypothesised relationships between constructs. The population comprised graduate and professional engineers who were registered under the Board of Engineers Malaysia (BEM). The purposive sampling method was employed for data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…However, very little scholarly research on TM practices and retention among engineers has been implemented (Nittala & Jesiek, 2018;Van Hoek & Schultz, 2013). Furthermore, very little research on TM practices and retention has been found in the manufacturing sector (Osman et al, 2017(Osman et al, , 2018Subramaniam et al, 2019). Most of the previous findings were found from sector of construction (Shikweni et al, 2019); education (Zeeshan, 2020); ICT (Ahmed & Yang, 2017); GLCs (Government-linked Companies) (Isa et al, 2018); private organisations (Singh & Sharma, 2015); hospital (Eltaybani et al, 2018).…”
Section: Problem Statementmentioning
confidence: 99%
“…However, very little scholarly research on TM practices and retention among engineers has been implemented (Nittala & Jesiek, 2018;Van Hoek & Schultz, 2013). Furthermore, very little research on TM practices and retention has been found in the manufacturing sector (Osman et al, 2017(Osman et al, , 2018Subramaniam et al, 2019). Most of the previous findings were found from sector of construction (Shikweni et al, 2019); education (Zeeshan, 2020); ICT (Ahmed & Yang, 2017); GLCs (Government-linked Companies) (Isa et al, 2018); private organisations (Singh & Sharma, 2015); hospital (Eltaybani et al, 2018).…”
Section: Problem Statementmentioning
confidence: 99%